Social Media Activities and the 212 Movement: The Indonesian Ulema Council’s Perspective - Iswandi Syahputra (Al-Jami'ah: Journal of Islamic Studies, 2020)
This article discusses the perspective of the Indonesian Ulema Council (Majelis Ulama Indonesia – MUI) regarding social media activities and the 212 Movement, referring to the Aksi Bela Islam (Action to Defend Islam) in Jakarta. MUI’s perspective is of utmost importance as MUI is seen as playing an important role in triggering the 212 Movement, which was carried out as a protest against the perceived religious blasphemy committed by the Jakarta Special Capital Region Governor at the time, Basuki Tjahaja Purnama (Ahok). MUI’s fatwa on Ahok subsequently led to a disagreement in defending religion or defending the state, and it had been openly and unrestrictedly debated among netizens on social media. Social media activities (chiefly Twitter) relating to this case had positioned MUI’s fatwa in numerous discussions that were littered with various expressions of hatred. This article aims to contribute a novel understanding pertaining to the relations between religion, ulema, fatwa, and social media activities. [Artikel ini membahas perspektif MUI terhadap aktifitas social media yang terkait dengan Aksi Bela Islam 212 di Jakarta. Pembahasan ini penting karena MUI dianggap berperan penting dalam memicu gerakan Aksi Bela Islam, yang merupakan protes terhadap Ahok karena dianggap telah melakukan penodaan agama. Fatwa MUI tersebut berakibat pada ketidaksetujuan dalam membela agama atau membela negara dan secara terbuka dan tidak terbatas memunculkan debat netizen di media sosial (utamanya Twitter), serta menjadi bahan diskusi yang mengarah pada ekspresi kebencian. Artikel ini juga menawarkan sebuah pemahaman baru terkait hubungan antara agama, ulama, fatwa dan aktivitas dalam media sosial.]